Burnout syndrome in healthcare professionals: an integrative literature review (Research, Society and Development, 2023)
Burnout Syndrome (BS) is understood as a result of excessive work overload, which is reflected mainly in healthcare professionals. The subject under study, Burnout at Work in healthcare professionals, is current and deserves attention, since it affects the general well-being and influences the subjective experience that in turn affects the decisions, attitudes and actions of the individual. This article aims to understand the influence of the Burnout Syndrome and its implications on the Quality of Life of healthcare professionals. It discusses Burnout in the Workplace of Healthcare Professionals, its causes, effects and highlights the importance of quality of life. This is an exploratory, quantitative and qualitative study of integrative review carried out in the Virtual Health Library (VHL) and PubMed databases. A total of 313 studies were found, and after applying the inclusion and exclusion criteria, 31 studies were included in this research. SB is a serious problem for health professional, generating complications that go beyond emotional stress, physical wear and directly interfere with the reduction in the quality of life of professionals. It was possible to evidence the relevance of actions to combat the pathology and possible actions that directly impact the improvement of Burnout symptoms in the short and long term. Thus, it is necessary to identify the precursors of this syndrome, to understand them, and thus promote interventions that aim to improve the quality of life of healthcare professionals.